Consumers´ decisionmaking under Salop´s model : Key study on Starbucks Prague and Richmond business model - Kučera, Oldřich; Čermáková, Klára; Čihák, Jakub; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This bachelor thesis analyses the Starbucks business model in Prague and Richmond, focusing on the company’s consumers and their decision-making. The main contribution of the thesis is the inverting of Salop’s circle model with an emphasis on having transportation costs as an endogenous variable. Using this modified Salop’s circle model, the transportation costs of the average Starbucks consumer in both cities are calculated, explained, and compared. It is revealed that the average Starbucks consumer in Richmond bears, on average, 1.255x higher transportation costs than the one in Prague and is willing to travel 2.54x higher distances to purchase the average Starbucks product. In addition, after analyzing transportation costs, the thesis offers a real-life applicable business proposal for where to place a new Starbucks store in both cities, based on several techniques often used in business consulting for solving case studies. The suggested most suitable location for the new store in Prague is the Prague main railway station. In contrast, in Richmond, it is the intersection of West Broad Street E and North Lombardy Street, close to Virginia Commonwealth University.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses